OQÍWSHÍLARDÍŃ KRITIKALÍQ PIKIRLEWIN RAWAJLANDÍRÍW - Babasheva, G. (SCIENCE and SOCIETY, 2025)
This article is about developing critical thinking. Also, the mechanism of critical thinking is studied in detail.